Lembaga Pemberdayaan Umat sebagai Aspek Reformatif Ekonomi Islam - Fuji Fitria Ningsih (Fakultas Dakwah IAIN Jember, 2020)
Changes that are hard to control are called development. Development is one of the solutions to the alleviation of poverty issues. Even Cambert argued that poverty actually lies in the so-called poverty trap (deprivation trap). The elements that exist in the deprivation trap are: the poverty itself, physical weakness, alienation or isolation, vulnerability and powerlessness. Normally, a number of creative institutions are provided to help those who are completely unable to support themselves. One of these institutions is an empowerment institution with the aim of developing the potential of the community by giving them motivation and counselling. The current study is trying to describe deeper about Islamic empowerment institutions as a reformative aspect of the ummah (community). This study collected the data by studying related scientific texts about the community empowerment institutions and Religious Studies and conducting field research. Therefore, the primary data were taken from the textbooks, articles, websites, news events, al-Qur'an and al-Hadith as well as various opinions from experts and scholars. In addition, data were also collected from the program implementations of the community empowerment institutions. Islam perceives society as a system which components/individuals need and support each other. Relationship among individuals in the community is ideally mutually beneficial. The economic gap can be a potential component that can be utilized to foster harmony and brotherhood among the community individuals. Islam encourages the implementation of community empowerment by adhering to 3 main principles, namely the principle of ukhuwwah (brotherhood), the principle of ta'awun (cooperation), and the principle of equality.